Promotion of female educators into managment positions at schools in Lulekani Circuit in the Mopani District, Limpopo Province, South Africa - Mathevula, N.S. (University of Limpopo (Turfloop Campus), 2014)
The purpose of the study is to explore the views of educators with regard to the promotion of female educators to management positions at primary schools in Lulekani Circuit in the Mopani District, Limpopo Province. Specifically, this research sought to identify the factors perceived by both men and women in management positions and those who are not in management positions to be the cause of the ongoing under-representation of women at school management level. At present there are many more female educators at primary schools in the Lulekani Circuit than there are male educators. However, to date in the circuit there are many more male educators occupying management positions at these primary schools than there are females. A qualitative research method in the form of semi-structured face-to face interviews was used in this study to investigate the perceived and actual barriers and challenges which impede the promotion of female educators to management positions at primary schools in the Lulekani Circuit in the Mopani District, Limpopo Province. Twenty participants, who included both male and female educators, from five primary schools participated in one-on-one, face-to-face interviews for the purpose of this study. The sample included educators who occupy management positions (principals, deputy principals and heads of departments) and those who do not occupy management positions. The study revealed that the under-representation of female educators in management position is a highly complex issue which is influenced by factors ranging from women’s lack of confidence, lack of support from colleagues and family, gender stereotyping, family commitments and pressure from conflicting roles. The exclusion of female educators from management positions is matter of concern because, not only does it exclude a significant section of the South African community from participating in decisions that directly affect them, but it also violates the principles of equality and of the creation of a non-sexist society which are enshrined in the South African Constitution. It is recommended that urgent steps be taken by all stakeholders to ensure equal representation of both male and female educators in management positions at schools. Keywords: Promotion, management position, barriers, leadership, underrepresentation, Gender, stereotypes, glass ceiling
Thesis (MPA) --University of Limpopo, 2013
Keywords: Promotion; Barriers; Leadership; Gender; Management position; Underrepresentation; Stereotypes; 353.535; Women teachers; Women executives; Women educators -- South Africa -- Biography